2019
DOI: 10.14449/jbd.2019.7.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Patients with Locally Advanced Breast Cancer Treated by Neoadjuvant Chemotherapy

Abstract: Purpose: Neoadjuvant chemotherapy (NAC) has become the standard treatment for patients with locally advanced breast cancer. The purpose of this study was to evaluate prognosis according to molecular subtype and clinicopathologic factors in patients with locally advanced breast cancer treated by NAC. Methods: We retrospectively analyzed the medical records of 91 patients with breast cancer who underwent NAC followed by surgery between January 2005 and January 2010. The patients were classified into four molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Most articles reported results similar to ours. Jaegal et al [29] reported a higher pCR in patients with a high histologic grade. Wang et al [30] and Shien et al [7] reported significantly higher rates of pCR in patients with nuclear grade 3 compared to those in patients with nuclear grades 1 or 2.…”
Section: Discussionmentioning
confidence: 95%
“…Most articles reported results similar to ours. Jaegal et al [29] reported a higher pCR in patients with a high histologic grade. Wang et al [30] and Shien et al [7] reported significantly higher rates of pCR in patients with nuclear grade 3 compared to those in patients with nuclear grades 1 or 2.…”
Section: Discussionmentioning
confidence: 95%